COASTAL COMMUNITIES' ADAPTATION TO DOMESTIC WATER NEEDS DUE TO TIDAL FLOODS IN TAMBAK LOROK AND KEMIJEN - Ika Fitri Andini; R Rijanta; Erlis Saputra (GeoEco, 2026)
Tambak Lorok and Kemijen in Semarang face chronic tidal flooding, land subsidence, and seawater intrusion that degrade groundwater, the leading domestic water source. Limited piped-water supply forces households to combine unsafe wells with bottled water to meet daily needs. Scientific gaps persist regarding integrated analyses of groundwater quality, household-level adaptation, and stakeholder roles at the village scale. This study aimed to analyse the quality of water used by communities affected by tidal flooding and to examine how coastal households adapt to fulfil domestic water needs in Tambak Lorok and Kemijen. A mixed quantitative–qualitative approach was applied through groundwater sampling and semi-structured interviews with 114 household respondents. The results show that 2 of 7 artesian well samples fall into the brackish category, with Electrical Conductivity values of 1,045 µmhos/cm in Tambak Lorok and 1,165 µmhos/cm in Kemijen. Other samples indicate fresh water transitioning to brackish, with EC values ranging from 663–937 µmhos/cm in Tambak Lorok and 912 µmhos/cm in Kemijen. Community adaptations include reliance on artesian wells (90.4%), universal use of gallon water for drinking and cooking (100%), and limited use of PDAM services (9.6%). In conclusion, degraded groundwater conditions directly shape household adaptation strategies and demonstrate uneven vulnerability across neighbourhoods. The findings imply the urgency of improving piped-water access, strengthening stakeholder coordination, and designing targeted interventions for chronically affected communities. Scientifically, this study contributes a novel village-scale integration of water-quality assessment, adaptation behaviour, and governance analysis, offering a comprehensive framework for coastal water management under tidal-flood pressures.